2009
DOI: 10.5380/acd.v10i1.21317
|View full text |Cite
|
Sign up to set email alerts
|

Estudo Da Influência De Justicia Acuminatissima (Miq.) Bremek. Sobre a Agregação Plaquetária E Coagulação Sanguínea

Abstract: Justicia acuminatissima (Miq.) Bremek (Acanthaceae) é uma espécie vegetal amplamente utilizada pela população do estado do Amazonas devido às suas propriedades medicinais antiinflamatórias. É conhecida popularmente como “sara-tudo” e suas folhas são utilizadas em decoctos, infusões e macerações. Baseado em relatos de seu uso, o presente trabalho avaliou a interferência da preparação extrativa das folhas obtida por maceração aquosa sobre agregação plaquetária e coagulação sanguínea. Nenhuma influência significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
1
1
0
1
Order By: Relevance
“…The results of evaluation of gastric lesions after exposition to high dose of PMFA are in agreement with clinical studies where non-selective NSAI was compared with COX-2 inhibitors and the ulcer index was observed, suggesting that PMFA might act by a mechanism independent of COX-1 inhibition (Kangwan et al, 2014). Emphasizing this, in a previous study we demonstrated that PMFA has no effect on platelet aggregation in vitro (Verdam et al, 2009), which is dependent on action of this enzyme (Dovizio et al, 2014).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The results of evaluation of gastric lesions after exposition to high dose of PMFA are in agreement with clinical studies where non-selective NSAI was compared with COX-2 inhibitors and the ulcer index was observed, suggesting that PMFA might act by a mechanism independent of COX-1 inhibition (Kangwan et al, 2014). Emphasizing this, in a previous study we demonstrated that PMFA has no effect on platelet aggregation in vitro (Verdam et al, 2009), which is dependent on action of this enzyme (Dovizio et al, 2014).…”
Section: Resultssupporting
confidence: 88%
“…Comparing the results of the evaluation of the anti-hyperalgesic and antiedematogenic activities of PMFA, it can be inferred that the popular reports of healing of inflammatory processes by users of the J. acuminatissima leaf teas are more directly related to pain relief, which is the most troublesome symptom of inflammation, since all tested doses were active. We previously showed that condensed tannins, coumarins and saponins form the majority of the secondary metabolites in J. acuminatissima leaves (Verdam et al, 2009). The Q5 saponins inhibit the glucocorticoid receptors, which are related to inflammatory response (Augustin et al, 2011).…”
Section: Resultsmentioning
confidence: 98%
“…, sendo confiável para inibir a inflamação por diferentes etiologias, seja de estímulo químico ou físico. Ressalte-se ainda que taninos condensados são descritos como bons antioxidantes (36,37). O grupo de pesquisa GERA (Grupo de Estudo em Lesão Renal) da Escola de Enfermagem da Universidade de São Paulo (EEUSP) vem desenvolvendo experimentos em modelo animal (ratos), com intervenções com plantas medicinais que atuam na nefroproteção da IRA induzida por isquemia, sepse, nefrotoxicidade, diabetes melitus, com resultados significativos na melhora da função renal e redução dos danos oxidativos (38)(39)(40)(41)(42).…”
unclassified